A Targeted Next-Generation Sequencing Mutation Panel for Pediatric Acute Myeloid Leukemia and Myelodysplastic Syndrome (MDS) Detects Potential Additional Driver Mutations in Pediatric GATA2-MDS - Fisher, Kevin E; Sayeed, Hadi; Lopez-Terrada, Dolores; Bertuch, Alison A; Gramatges, Maria Monica (Blood, 2015)
Introduction: In adult populations, driver mutations often facilitate the progression of myelodysplastic syndrome (MDS) to acute myeloid leukemia (AML). Increased mutational burden is associated with decreased leukemia-free survival (Papaemmanuil et al, 2013); however, this phenomenon is less common in pediatric MDS. GATA2 mutations resulting in loss of function or haploinsufficiency are associated with MDS predisposition. Recent reports in adults with GATA2-MDS suggest that additional somatic driver mutations such as ASXL1, EZH2, and GATA1 contribute to rapidly progressive disease (Bodor et al, 2012; Fujiwara et al, 2014). Yet the spectrum of somatic mutations in pediatric GATA2-MDS is not well described. We applied a custom next-generation sequencing (NGS) panel inclusive of germline and acquired mutations commonly reported in pediatric AML/MDS to a subset of MDS patients with germline GATA2 mutations. Our results indicate that acquisition of somatic mutations in AML/MDS related genes may contribute to pediatric GATA2-MDS disease evolution and pathogenesis. Methods: Using Agilent SureDesign, we designed an NGS panel that targeted genes frequently mutated in pediatric AML/MDS, including 278 exonic, promoter, or intronic regions from 46 genes. Select known mutations in diagnostic specimens from a local pediatric AML/MDS cohort were used for panel validation. We applied this panel to DNA extracted from blood or marrow samples from 4 pediatric subjects diagnosed at ages 5-15 years with GATA2-MDS, and one subject age 8 with suspected GATA2-MDS. Sample NGS libraries were prepared, multiplexed, and sequenced on MiSeq flow cells in paired-end mode. Read alignment, variant calling, and annotation were performed using Agilent SureCall v3.0 software and NExtGENe software. Variants passing defined QC metric filters were reviewed for pathogenic significance. This research was performed under a local Institutional Review Board-approved protocol and in accord with the Declaration of Helsinki. Results: The subject with suspected GATA2-MDS was confirmed to have a deletion in GATA2 resulting in a frameshift. Presumed germline variants in telomerase reverse transcriptase (TERT) were found in one subject at allele frequencies consistent with heterozygosity. Four acquired mutations were found in two out of five GATA2-MDS subjects: a deletion in IKZF1 resulting in a frameshift, and mutations in both RUNX1 (n=2) and in SETBP1 (Table 1). Conclusions: Within a cohort of five GATA2-MDS subjects, we found four somatic mutations likely contributing to disease pathogenesis.Acquired mutations in SETBP1, including p.G870S, are an independent and poor prognostic indicator in adult AML (Makishima et al, 2013). Acquired mutations in RUNX1 are also common in adult MDS/AML, and both p.L56S and p.D198Gmutations have been described in adult cases of MDS progressing to AML (Pellagati et al, 2015). We also identified a frameshift mutation in IKZF1 presumed to be somatic in one subject. Large focal deletions, but not frameshifts, have been described as rare but recurrent events in pediatric AML in conjunction with monosomy 7, as with this case (de Rooij et al, 2015). Our results represent the first evidence of acquired driver mutations in pediatric GATA2-MDS, and demonstrate the utility of this comprehensive custom AML/MDS NGS panel to uncover key somatic mutational events that may be associated with rapidly progressive disease. [Display omitted] No relevant conflicts of interest to declare.